An ontological analysis of education from the contributions of Badiou and Rancière - Colella, Leonardo (Estudios de Filosofía, 2016)
This paper proposes to explore the educational process from the Alain Badiou ontology and theory of the subject. To do so, aims to analyze the educational situations not from the pedagogical triangle figure, but rather on the bases of a meeting of individuals with dual characterization: “equality” and “thinking”. Thereby, incorporates alternative experiences to institutionalized education to the educational analysis, as the case of Jacotot, and the Jacques Rancière’s appropriation of it. Also, the article aims to characterize the concept of “subject” in education, from a disruption of distributional criteria associated to the alternative experiences and the Rancière’s critiques of the founding principles of modern education.